Study of Rainfall and Water Discharge Spatial Variability Using Exploratory Spatial Data Analysis Method in Bondowoso Regency - Faillasuf, Vide Mirza; Halik, Gusfan; Wiyono, Retno Utami Agung (BERKALA SAINSTEK, 2021)
The difference in rainfall intensity affects the hydrological cycle as a process that greatly determines the amount of water discharge. Thus, in water resources management, it is important to determine the distribution pattern of rainfall and discharge. By studying the characteristics of rainfall distribution patterns and water discharge, the potential of water resources can be illustrated well. This study uses the Exploratory Spatial Data Analysis method to examine spatial variability of rainfall intensity and water discharge in Bondowoso Regency. Rainfall and discharge data are collected from 35 rain stations and 227 weirs in 2008 until 2018. This study produces monthly average rainfall distribution values between 190 mm / month with monthly average discharge between 7300lt/sec/month. Meanwhile, the obtained average annual rainfall distribution values are between 2300 mm/year with annual average discharge values between 105000 lt/sec/month. The spatial distribution map using IDW method produces information on the potential of water resources as follow: the higher the height of a place, the higher the average monthly rainfall, while the lower the height of a place, the higher the average monthly discharge. As for the obtained correlation value between rainfall and discharge is R² = 0.665.